A multi‐MHz single‐shot data acquisition scheme with high dynamic range: pump–probe X‐ray experiments at synchrotrons. (10th October 2016) - Britz, Alexander; Assefa, Tadesse A.; Galler, Andreas; Gawelda, Wojciech; Diez, Michael; Zalden, Peter; Khakhulin, Dmitry; Fernandes, Bruno; Gessler, Patrick; Sotoudi Namin, Hamed; Beckmann, Andreas; Harder, Manuel; et al.
Abstract : A time‐resolved X‐ray absorption spectroscopy setup has been developed and tested, comprising a synchronized MHz fiber amplifier laser system with a multi‐MHz data acquisition scheme capable of detecting multi‐photon events in a single X‐ray photon pulse. This system permits recording time‐resolved X‐ray absorption spectra with quasi‐static signal quality. Abstract : The technical implementation of a multi‐MHz data acquisition scheme for laser–X‐ray pump–probe experiments with pulse limited temporal resolution (100 ps) is presented. Such techniques are very attractive to benefit from the high‐repetition rates of X‐ray pulses delivered from advanced synchrotron radiation sources. Exploiting a synchronized 3.9 MHz laser excitation source, experiments in 60‐bunch mode (7.8 MHz) at beamline P01 of the PETRA III storage ring are performed. Hereby molecular systems in liquid solutions are excited by the pulsed laser source and the total X‐ray fluorescence yield (TFY) from the sample is recorded using silicon avalanche photodiode detectors (APDs). The subsequent digitizer card samples the APD signal traces in 0.5 ns steps with 12‐bit resolution. These traces are then processed to deliver an integrated value for each recorded single X‐ray pulse intensity and sorted into bins according to whether the laser excited the sample or not. For each subgroup the recorded single‐shot values are averaged over ∼10 7 pulses to deliver a mean TFY value with its standard error for each data point, e.g. at a given X‐ray probe energy. The sensitivity reaches down to the shot‐noise limit, and signal‐to‐noise ratios approaching 1000 are achievable in only a few seconds collection time per data point. The dynamic range covers 100 photons pulse −1 and is only technically limited by the utilized APD.